The new challenge: End all forms of malnutrition by 2030 - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
It is a formidable challenge. Every country is facing a serious public health challenge from malnutrition (IFPRI 2014). One in three people is malnourished in one form or another (IFPRI 2015a). Malnutrition manifests itself in many forms: as children who do not grow and develop to their full potential, as people who are skin-and-bone or prone to infection, as people who carry too much weight or whose blood contains too much sugar, salt, or cholesterol.